VIETNAM: 'N BLOEDIGE LEERSKOOL - Conradie, D. (Scientia Militaria - South African Journal of Military Studies, 2012)
The sudden collapse of South Vietnam on 30 April 1975 came as a surprise to most observers. The general expectation of a 'small' Vietnam centred around Saigon and finally succumbing after years of bitter fighting, proved to be a pipe dream. The Republic of South Vietnam collapsed in a heap of chaos, and brought to an end a war that spanned three decades. It was also the United States of America's first major defeat. This article provides insight into the reasons for the defeat.